Antidiabetic Potential of Mushroom-Based Herbal Formulation in Streptozotocin-Induced Diabetic Rats - Bisma Saleem; Ghulam Hussain; Azhar Rasul; Haseeb Anwar; Mudassir Hassan (Scientifica)
Diabetes mellitus, a high-morbidity endocrine disease, is typically treated with synthetic hypoglycemic drugs that are costly and have severe side effects. Natural products, like mushrooms, offer a cost-effective, accessible, and eco-friendly alternative. Current study intends to examine the antidiabetic potential of mushroom-based herbal formulation (MHF) on streptozotocin-induced diabetic rats. For this purpose, five different groups of Wister rats were established including one normal group. Among four diabetic groups, one group served as the diabetic control, while the remaining two groups were administrated with MHF 200 mg/kg and 400 mg/kg, respectively, and the fifth was administered with metformin for 28 days. On the last day of experiment, all rats were sacrificed, and samples were collected for different analysis. The study outcomes revealed that the administration of MHF to diabetic rats resulted in remarkable (p<0.001) improvements in fasting blood glucose (FBG) levels and glycated hemoglobin along with other biochemical markers. The histopathological examination also showed the protective effect of MHF against diabetic-induced damage in the pancreas, kidney, and liver. It also helps in the regeneration of β-cells in the pancreas. These findings suggest MHF is a safer and more effective alternative for managing diabetes.